Adjuvant Effect of Quillaja saponaria Saponin (QSS) on Protective Efficacy and IgM Generation in Turbot (Scophthalmus maximus) upon Immersion Vaccination - Yujuan Wang; Xiuhua Wang; Jie Huang; Jun Li (International Journal of Molecular Sciences, 2016)
The adjuvant effect of Quillaja saponaria saponin (QSS) on protection of turbot fry was investigated with immersion vaccination of formalin-killed Vibrio anguillarum O1 and various concentrations of QSS (5, 25, 45 and 65 mg/L). Fish were challenged at days 7, 14 and 28 post-vaccination. Significantly high relative percent of survival (RPS) ((59.1 ± 13.6)%, (81.7 ± 8.2)%, (77.8 ± 9.6)%) were recorded in the fish that received bacterins immersion with QSS at 45 mg/L, which is comparable to the positive control group vaccinated by intraperitoneal injection (IP). Moreover, a remarkably higher serum antibody titer was also demonstrated after 28 days in the vaccinated fish with QSS (45 mg/L) than those vaccinated fish without QSS (p < 0.05), but lower than the IP immunized fish (p < 0.05). Significant upregulation of IgM gene expression has also been identified in the tissues of skin, gill, spleen and kidney from the immunized fish in comparison to the control fish. Taken together, the present study indicated that QSS was able to dramatically evoke systemic and mucosal immune responses in immunized fish. Therefore, QSS might be a promising adjuvant candidate for fish vaccination via an immersion administering route.